A triple helix case: Innovative and sustainable international summer school in China - Jabbar Al-Obaidi; Chien Wen Yu (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: This article explored the International Summer School model in China. Its goals are to evaluate the curriculum and its features and to analyze how the Triple Helix Theory of Innovation is used. In the summer of 2019, Uni vPlus-BSU Shanghai Program and UnivPlus-FSU Beijing Program students were surveyed. Methodology: One hundred fifteen students from BSU (Shanghai) and FSU (Beijing) were given a survey consisting of 13 questions. The authors gathered information on the summer programmes’ effectiveness by surveying both students and teachers. Volunteers from each campus filled out the survey, resulting in a skewed sample. Findings: UnivPlus is one of the leading organisations providing international summer schools in China for Chinese international students attending universities in the United States and Canada and using their summer breaks in China to study and earn transfer credits. Innovation through collaboration between the academic world and private and public sectors is called the "Triple Helix Model." The recent rise of Chinese initiatives to host international summer schools is a prime example of the Triple Helix innovation model at work. The research presented in this paper shows a positive connection between the cooperation of educational institutions in the United States, China, and Canada, efficient time management, intrinsic motivation, and qualitative faculty support. Our findings reflect the motivations of all involved to boost academic innovation and competition for the betterment of student learning and the development of their knowledge and intercultural competencies. Implications/Novel Contribution: The program’s success has prompted BSU administrators to consider expanding the initiative to include summer sessions in Japan and Jordan. Through the international summer programme, Chinese students can earn credit at their home universities for courses taken while they are in their home country during the summer to visit family. The approval procedure here is simple and beyond reproach.